Physical and microstructure properties of oyster mushroom-soy protein meat analog via single-screw extrusion - Mohamad Mazlan, Mazween; A. Talib, Rosnita; Nyuk, Ling Chin; Shukri, Radhiah; Taip, Farah Saleena; Mohd Nor, Mohd Zuhair (Multidisciplinary Digital Publishing Institute, 2020)
Single-screw extrusion of a fibrous-structured meat analog from soy proteins added with low-grade oyster mushroom was successful. Satisfactory extrudates were obtained at a barrel temperature of 140 °C, screw speed range of 100–160 rpm, and oyster mushroom addition at 0%, 7.5%, and 15% via factorial experiments. Single-screw extrusion equipped with a slit die successfully produced expanded oyster mushroom-soy protein extrudates. However, the increase in the oyster mushroom content significantly decreased (p ≤ 0.05) the expansion ratio of the extrudate from 1.26 to 0.98. This result indicated that adding more oyster mushroom restrained the expansion ratio. The extrudates had a medium density range (max of 1393.70 ± 6.30 kg/m3). By adding oyster mushroom, the extrudates attained a higher moisture content (range = 34.77% to 37.93%) compared with the extrudates containing the protein mixture only (range = 26.99% to 32.33%). The increase in screw speed and oyster mushroom significantly increased (p ≤ 0.05) the water absorption index. The increase in the texturization index was significantly influenced (p ≤ 0.05) by oyster mushroom addition rather than the screw speed. A defined fibrous structure supported the high texturization index and small shape of air cells observed in the extrudates.